The correlation between professional competencies and self-efficacy among nursing students and registered nurses. An observational cross-sectional study - Prendi, Emanuela; Stievano, Alessandro; Caruso, Rosario; Duka, Blerina; Spada, Florian; Rocco, Gennaro; Notarnicola, Ippolito (Acta Biomedica Atenei Parmensis, 2024)
Background and aim of the work: The assessment and application of professional skills in registered nurses and undergraduate nursing students during clinical practice are essential in nursing education. Self-efficacy positively affects the professional competence of nursing students and registered nurses, but studies have yet to focus on the relationship between professional competence and self-efficacy. This study examined professional competence and its association with self-efficacy among undergraduate nursing students and registered nurses. Research and Methods: A cross-sectional, observational, and correlational study was conducted through a two-questionnaire-based survey. Sampling was conventional. Data was collected through the Italian version of the Nurses’ Professional Competence Scale Short Form (I-NPCS-SF), which investigates professional competencies, and Nursing Professional Self-Efficacy Scale (NPSES), which investigates self-efficacy and a socio-demographic questionnaire. The study was based on a convenience sample of 320 individuals: nursing students (n=116) in Albania and Italian nurses (n=204). Results: Factors associated with professional competence, particularly ethical values, of nursing students (M = 77.57) and registered nurses (M = 83.18) obtained the lowest average score, while other factors were almost the same for the two groups of nurses. Self-efficacy did not play an essential role in the development of professional competence of nursing students and registered nurses, as our investigation found no correlation between these two elements. Conclusions: The results of this study can be applied as a reference for improving nursing education programs by augmenting students’ professional competence and, consequently, future nurses.